The Effecting of Various Parameters on the Thermophysical and Rheological Properties of SiO2 Nano-lubricating Oil in Petroleum Refineries - Awad, Alyaa M.; Sukkar, khalid A.; Jaed, Dalya M. (Journal of Petroleum Research and Studies, 2022)
The improvement of the performance of automotive engines necessitated the use of effective lubricating oil. Experimentally explored are the thermophysical characteristics and rheological behavior of Nano-lubricating oil made by mixing SiO2 nanoparticles with stock-60. Nano-lubricant has been prepared with a two-step method using a magnetic stirrer as a first step mixing and an ultrasonic homogenizer. The rheological properties were investigated at various shear rates, temperature, and solid volume percent. This research was carried out on concentrations ranging from 0.1 % to 1.0 %. The results showed elevation in temperature, the dynamic viscosity dropped in all shear rates due to lower SiO2 NP concentrations and that all samples exhibited Newtonian behavior at all temperatures fixed. The thermal conductivity of nano-lubricating oil was tested at various temperatures ranging from 20°C to 50°C. The different solid volume percent of SiO2 NPs were in the range of 0 to 1% maximum enhancement value was achieved at higher temperature with increased volume percent of SiO2 NPs. Other important thermophysical properties of lube oil including flashpoint and pour point were also measured. The results revealed that adding SiO2 NPs to stock-60 at a solid volume percent of 1% will result in a maximum improvement of 12 % in flashpoint over the base oil, while the improvement of pour point was achieved at nano-addition of 0.75% and 1% compared with the base oil was increased from -3°C to -6°C.